German-Israeli Political Relations under the Chancellor's Government Willy Brandt (1969-1974 AD) - Al-Shanaq, Abdul Majeed Zaid (Dirasat: Human and Social Sciences, 2023)
Objectives: This study examines the evolution of German-Israeli political relations under Chancellor Willy Brandt's government (1969-1974 AD). The government, led by the Social Democratic Party (SPD), was formed after the parliamentary elections on 9/28/1969 AD and gained confidence through an alliance with the Free Democratic Party (FDP), led by Walter Scheel. Methods: The study employed an analytical historical approach, drawing from unpublished German documents in the archives of the German Ministry of Foreign Affairs and other contemporary sources to shed light on an under-researched subject. It analyzes Germany's progression from establishing normal relations in 1969 AD to further developments by 1974 AD. Results: The study reveals that political relations with Israel evolved in line with Germany's policy of openness to the socialist camp. It also examines how the German government dealt with the "Munich Process" during the Olympic Games and its impact on Israel-Germany relations. Additionally, the study explores the factors influencing Germany's stance during the October 1973 war, particularly in light of the Arab oil initiative led by King Faisal Al Saud in foreign policy. Conclusions: During Chancellor Willy Brandt's government, German-Israeli political relations advanced significantly, with Germany expressing support for Israeli political positions. Moreover, the study highlights the reestablishment of German-Arab relations, which had been severed since 1965 AD.